APPLICATIONS OF ACTOR-NETWORK THEORY IN ISLAMIC EDUCATION:: A Systematic Literature Review - Wiryawan, M. Ryzki; Permana, Johar; Suryana, Asep; Suryadi, Suryadi; Enbeyle, Wegayehu (Conciencia, 2025)
Actor-Network Theory (ANT) is a sociological framework that explores how relationships between human and non-human entities (actors) form networks that shape social, scientific, and technological practices. This study presents a comprehensive bibliometric analysis of research on Actor-Network Theory (ANT) and its application in education between 2010 and 2024, based on 442 documents retrieved from the SCOPUS database. Data processing was carried out using SCOPUS analysis tools, VOSviewer, and Biblioshiny.The findings reveal a steady growth in publications, particularly influenced by key contributors such as Tara Fenwick, who has played a pivotal role in introducing ANT to educational theory and practice. Although the annual growth rate of publications has declined in recent years, ANT continues to serve as a valuable framework for analyzing the complex interactions among human and non-human actors in educational environments. The most active countries in ANT-education research include the United Kingdom and Australia, with institutions such as Victoria University and Linköping University leading in output. Keyword analysis identified three dominant thematic clusters—conceptual/philosophical, institutional/applied, and methodological—demonstrating ANT’s versatility. Future research directions suggest expanding ANT studies into underrepresented regions like Asia, exploring informal and vocational learning contexts, and embracing emerging methodologies such as digital ethnography and participatory design. This review affirms ANT’s relevance in rethinking education within increasingly networked and technologically mediated landscapes.